Association of survival with adjuvant chemotherapy in patients with stage IB gastric cancer: a multicentre, observational, cohort studyResearch in context - Xianchun Gao; Gang Li; Jingyu Deng; Lulu Zhao; Weili Han; Nannan Zhang; Yunhe Gao; Linbin Lu; Shibo Wang; Jun Yu; Junya Yan; Gan Zhang; et al. (Elsevier, 2024)
Summary: Background: Recurrence following radical resection in patients with stage IB gastric cancer (GC) is not uncommon. However, whether postoperative adjuvant chemotherapy could reduce the risk of recurrence in stage IB GC remains contentious. Methods: We collected data on 2110 consecutive patients with pathologic stage IB (T1N1M0 or T2N0M0) GC who were admitted to 8 hospitals in China from 2009 to 2018. The survival of patients who received adjuvant chemotherapy was compared with that of postoperative observation patients using propensity score matching (PSM). Two survival prediction models were constructed to estimate the predicted net survival gain attributable to adjuvant chemotherapy. Findings: Of the 2110 patients, 1344 received adjuvant chemotherapy and 766 received postoperative observation. Following the 1-to-1 matching, PSM yielded 637 matched pairs. Among matched pairs, adjuvant chemotherapy was not associated with improved survival compared with postoperative observation (OS: hazard ratio [HR], 0.72; 95% CI, 0.52-1.00; DFS: HR, 0.91; 95% CI, 0.64-1.29). Interestingly, in the subgroup analysis, reduced mortality after adjuvant chemotherapy was observed in the subgroups with elevated serum CA19-9 (HR, 0.22; 95% CI, 0.08-0.57; P = 0.001 for multiplicative interaction), positive lymphovascular invasion (HR, 0.32; 95% CI, 0.17-0.62; P < 0.001 for multiplicative interaction), or positive lymph nodes (HR, 0.17; 95% CI, 0.07-0.38; P < 0.001 for multiplicative interaction). The survival prediction models mainly based on variables associated with chemotherapy benefits in the subgroup analysis demonstrated good calibration and discrimination, with relatively high C-indexes. The C-indexes for OS were 0.74 for patients treated with adjuvant chemotherapy and 0.70 for patients treated with postoperative observation. Two nomograms were built from the models that can calculate individualized estimates of expected net survival gain attributable to adjuvant chemotherapy. Interpretation: In this cohort study, pathologic stage IB alone was not associated with survival benefits from adjuvant chemotherapy compared with postoperative observation in patients with early-stage GC. High-risk clinicopathologic features should be considered simultaneously when evaluating patients with stage IB GC for adjuvant chemotherapy. Funding: National Natural Science Foundation of China; the National Key R&D Program of China.